Холівські дослідження провідних каналів, сформованих у германії пучками легких іонів високих енергій - Lysochenko, S.V.; Zharkikh, Yu.S.; Kukharenko, O.G.; Tretiak, O.V.; Tolmachov, M.G. (Publishing house "Academperiodika", 2021)
The implantation of the high-energy ions of H+ or He+ in germanium leads to the creation of buried conductive channels in its bulk with equal concentrations of acceptor centers. These centers are the structure defects of the crystal lattice which arise in the course of deceleration of high-energy particles. This method of introducing electrically active defects is similar to the doping of semiconductors by acceptor-type impurities. It has been established that the density of defects increases with the implantation dose till ≈5×10^15 cm−2. The further increase of the implantation dose does not affect the level of doping. In the range of applied doses (10^12–6×10^16) cm−2, the Hall mobility of holes in the formed conducting channels is practically independent of the implanted dose and is about (2-3)×10^4 cm2/Vs at 77 K. The doping ofthe germanium by high-energy ions of H+ or He+ to obtain conducting regions with high hole mobility can be used in the microelectronics technology.